If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6d+13=10d-3
We move all terms to the left:
6d+13-(10d-3)=0
We get rid of parentheses
6d-10d+3+13=0
We add all the numbers together, and all the variables
-4d+16=0
We move all terms containing d to the left, all other terms to the right
-4d=-16
d=-16/-4
d=+4
| 22*36=20x | | 3x²+6x+8=0 | | x-7=(-8) | | 5x-13=3x+39 | | x/5+3=1/3 | | 70*66=110x | | 8x2+80x=0 | | 7a+9=-5 | | 2x-1=5x+15 | | -9j+6=-10 | | 21*62=28x | | |n+14|=20 | | (10x+7)/4x=2 | | 0+8y=20 | | (4x+1)=2x2+4 | | 6x+18,6=0 | | 8(10p-3)=-3(-6p-8)-10p | | 44b/5=8 | | 18^{x+5}=18^9 | | 4(x-1)+3=2x-(5x+6) | | h=4+21(10)+16(10)^2 | | 2^2x-6∙2^x+8=0 | | 180(X+15)-0.4(X+15)=180x | | 7/(7b+4)=2/b-4 | | 2m5=10 | | x-(-2.7)=1 | | 3x•2x=5-3 | | x^2+0.75x^2=19^2 | | 16x2−8x+145=0 | | x-(2)(5)=12 | | 4.2*5.4=9x | | X-3x/2=35 |